Validating Test of Science-Related Attitudes (TOSRA) For Elementary Students In Mataram, Indonesia - Rindu Rahmatiah; Joni Rokhmat; A. Wahab Jufri; Gunawan; AA Sukarso (Postgraduate Program, University of Mataram, 2023)
The Test of Science-Related Attitudes (TOSRA) was initially developed in Australia by Barry J. Fraser in 1977 for high school students. This research aims to modify and validate the TOSRA used for 5th-grade elementary school students in Mataram, Indonesia. A survey model with a Likert scale questionnaire was used in the research and a purposive sampling strategy was used to recruit 318 students from 3 different elementary schools in Mataram. There were 4 of 7 indicators of TOSRA used in this research: attitude to scientific inquiry, adoption of scientific attitudes, enjoyment of science lessons, and leisure interest in science. From each indicator, 5 of the 10 statements on TOSRA are taken, so a total of 20 statements were presented in the questionnaire. Each item of the question was analyzed for its validity and reliability overall. The results showed that all question items are valid and reliable so this modified TOSRA can measure the science-related attitudes of 5th-grade elementary school students in Mataram, Indonesia.